Competition and stereotypic behavior in thoroughbred horses: The value of saliva as a diagnostic marker of stress - Bazzano, M.; Marchegiani, A.; La Gualana, F.; Petriti, B.; Petrucelli, M.; Accorroni, L.; Laus, F. (PLOS ONE, 2024)
Many horses exhibit stereotypies, especially when living in human controlled environments that may prevent horses from satisfying natural needs in terms of feeding, drinking, moving, and socializing. In human medicine, obsessive compulsive disorder and other severe psychiatric disturbances are associated with stereotypic behaviors; salivary biomarkers evaluation is considered a reliable tool for diagnosis of common mental health disorders because saliva collection easy to obtain and noninvasive. In this study, we hypothesized that salivary cortisol concentrations, in addition to alpha-amylase (sAA) and butyrylcholinesterase (BChE) activities, are considered stress biomarkers that may be influenced in horses trained for racing competition with stereotypic behaviors. Saliva at rest condition was obtained from ten non-stereotypic Thoroughbreds horses involved in high-level competition; eleven Thoroughbreds high-level competition horses showing stereotypic behaviors, and five Thoroughbreds leisure non-competition horses. Cortisol was found to be higher in high-level competition non-stereotypic horses and sAA was significantly higher in non-stereotypic leisure horses when compared to horses involved in competition, while BChE did not change between groups. These results may represent the basis for further behavioural evaluation to elucidate how stereotypic horses and horses involved in competition overcome stressful situations.